Medications used disproportionately during pregnancy: Priorities for research on the risks and benefits of medications when used during pregnancy. Issue 1 (16th September 2020) - Havard, Alys; Barbieri, Sebastiano; Hanly, Mark; Perez‐Concha, Oscar; Tran, Duong T.; Kennedy, Debra; Jorm, Louisa R.
Abstract: Purpose: To identify medications used disproportionately more or less among pregnant women relative to women of childbearing age. Methods: Medication use among pregnant women in New South Wales, Australia was identified using linked perinatal and pharmaceutical dispensing data from 2006 to 2012. Medication use in women of childbearing age (including pregnant women) was identified using pharmaceutical dispensing data for a 10% random sample of the Australian population. Pregnant social security beneficiaries (n = 111 612) were age‐matched (1:3) to female social security beneficiaries in the 10% sample. For each medication, the risk it was dispensed during pregnancy relative to being dispensed during an equivalent time period among matched controls was computed. Medications were mapped to Australian pregnancy risk categories. Results: Of the 181 included medications, 35 were statistically significantly more commonly dispensed to pregnant women than control women. Of these, 23 are categorised as posing no increased risk to the foetus. Among medications suspected of causing harm or having insufficient safety data, the strongest associations were observed for hydralazine, ondansetron, dalteparin sodium and ranitidine. Use was less likely during pregnancy than control periods for 127 medications, with the strongest associations observed for hormonal contraceptives and progestogens. Conclusions: Most medications found to be used disproportionately more by pregnant women are indicated for pregnancy‐related problems. A large number of medications were used disproportionately less among pregnant women, where avoidance of some of these medications may pose a greater risk of harm. For many other medications avoided during pregnancy, current data are insufficient to inform this risk‐benefit assessment.